A quantum wave packet study of the ND+D reaction - Surucu, Seda; Tasmanoglu, Gulsen; Akpinar, Sinan (Taylor & Francis Ltd, 2012)
We present the quantum scattering dynamics of the depletion reaction ND (a (1)Delta)+D'-> N(D-2)+D-2 and of the exchange reaction ND (a (1)Delta)+D'-> ND'(a (1)Delta)+D using the real wave packet and flux methods and modified NH2 A(2)A(1) potential energy surface (PES). A quantum scattering dynamics calculation is used to study the initial-state-resolved reaction probabilities, integral cross section, rate constants and thermal rate constant for both channels using the centrifugal sudden (CS) approximation for non-zero total angular momentum (J) values. Integral cross sections for both reactions depend strongly on the initial rotational states. In particular, the thermal reaction rate constant for the depletion channel is in good agreement with experimental and semiclassical results.
Keywords: depletion reaction; exchange reaction; initial state resolved probabilities; thermal rate constant